STRATEGI PENGELOLAAN ASET WAKAF DALAM MENGURANGI TINGKAT PENGANGGURAN DI JAWA BARAT - Luqmanurrifqiansyah, Amar; Wegati, Sri; Fauziah Ardiningrum, Dalilah (Program Studi Ekonomi Syariah, 2024)
Humans in applying human thinking, including in economic matters. Muslim intellectual figures used two main sources, namely the Koran and Hadith, to solve several economic problems that began to emerge after the death of the Prophet. Apart from being famous as the father of Islamic ethics, Ibn Miskawaih also contributed his thoughts to economics. Apart from Ibn Miskawaih's thoughts in education, there are also his thoughts in economics. One of his thoughts in economics is about the concept of money exchange and the role of money. The approach to writing used is to use the qualitative method of library research (Library Research). The results of the study show that humans are social creatures who need each other the most to fulfill their needs for goods and services. Therefore, humans will exchange goods and services with appropriate compensation (reward, al-mukafat al-mukafat almunasihab). When exchanging money, it will act as a tool of assessment and balancing (al-muqawwim al-musawwi baynahuma) in the exchange, so that justice can be created